Toward a theoretical brain-model. - Precker, Joseph A.; PRECKER, J A (Journal of Personality)
The article focuses on a theoretical brain-model. The emergence of similar ideas at critical moments is always a source of interest for the observer of the cultural process. Men working independently, with different aims and orientation, seem to emerge with similar or related formulations, which need only reorganization and integration to answer major theoretical issues. This process seems to be going on in the field of psychological theory today and the aim of the paper is to attempt to organize several related formulations into one consistent framework. A call from several quarters recently has indicated the need for a useful and meaningful theoretic brain-model. Four recent contributors to psychological understanding have presented material, which awaits synthesis. These contributors are: David Krech, Donald O. Hebb, Norbert Wiener and Walter Coutu. A brief presentation of the major points of view of these men must be given before any integration is possible. Three of the four are concerned, directly or indirectly, with neurophysiological processes and models, only Coutu does not deal with them, but it will be indicated that there are implicit assumptions related to neural processes, which shed light on the problem.